2017
DOI: 10.3847/1538-3881/153/1/44
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Inner Disk Around Hd 141569 a From Keck/Nirc2 L-Band Vortex Coronagraphy

Abstract: HD 141569 A is a pre-main sequence B9.5 Ve star surrounded by a prominent and complex circumstellar disk, likely still in a transition stage from protoplanetary to debris disk phase. Here, we present a new image of the third inner disk component of HD 141569 A made in the L' band (3.8 µm) during the commissioning of the vector vortex coronagraph recently installed in the near-infrared imager and spectrograph NIRC2 behind the W.M. Keck Observatory Keck II adaptive optics system. We used reference point spread f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 47 publications
17
61
0
Order By: Relevance
“…It shows H I emission lines, has an extended disk in scattered light (e.g., Weinberger et al 1999), and has a mid-infrared excess (e.g., Malfait et al 1998). However, this IR excess is within a factor of a few of βPic (Clampin et al 2003), indicating that it may straddle the transition from gas-rich accretion disk to debris disk (e.g., Mawet et al 2017). This makes the stellar accretion rate inferred from the Hα emission, 10 −8 M ☉ yr −1 , surprising (Mendigutía et al 2017b).…”
Section: Appendix D Comment On Individual Systemsmentioning
confidence: 99%
“…It shows H I emission lines, has an extended disk in scattered light (e.g., Weinberger et al 1999), and has a mid-infrared excess (e.g., Malfait et al 1998). However, this IR excess is within a factor of a few of βPic (Clampin et al 2003), indicating that it may straddle the transition from gas-rich accretion disk to debris disk (e.g., Mawet et al 2017). This makes the stellar accretion rate inferred from the Hα emission, 10 −8 M ☉ yr −1 , surprising (Mendigutía et al 2017b).…”
Section: Appendix D Comment On Individual Systemsmentioning
confidence: 99%
“…We find a relatively low value for the Henyey-Greenstein parameter of anisotropic scattering, with =  | | g 0.17 0.13, indicative of grains favoring forward scattering. This value is expected for a disk of moderate inclination such as HD104860, which does not Golimowski et al 2011;Mawet et al 2017). As mentioned before, this may not be representative of the SPF at smaller scattering angles, as it was shown that, for some dust grains, it may significantly differ from a HenyeyGreenstein model and sharply peak at angles below 40°despite a relatively flat phase function at large angles (Hedman & Stark 2015; Milli et al 2017b).…”
Section: Hd104860 Analysismentioning
confidence: 88%
“…Even so, progress is being made in the fields of direct imaging of exoplanets [1] and characterization of proto-star systems [2,3]. This progress is likely to accelerate due to a new generation of 30 m-class telescopes, such as the European ELT, already under construction.…”
Section: Introductionmentioning
confidence: 99%
“…A method for increasing or decreasing the depth of the grating for the L-band has been developed [7], which allows optimization of the phase mask rejection ratio. The phase masks have been installed in infrared coronagraphic instruments (N-and L-band) on several 10-m class telescopes (VLT/NACO [8], VLT/VISIR [9], LBT/LMIRCam [10] and Keck/NIRC2 [1][2][3]) around the world. Following the success of these infrared coronagraphs, AGPMs for the NIR (1-3 μm) and ultimately for VIS (400-700 nm) spectral bands have become attractive, in particular for current high contrast instruments like VLT/SPHERE.…”
Section: Introductionmentioning
confidence: 99%